Students' and lecturers' perspectives on the implementation of online learning in medical education due to COVID-19 in Germany: a cross-sectional pilot study - Hertling, Stefan F.; Back, David A.; Kaiser, Mario; Loos, Franziska M.; Schleußner, Ekkehard; Graul, Isabel (Frontiers in Medicine, 2023)
Background During the coronavirus disease 2019 (COVID-19) crisis, many things changed in universities around the world. In-person learning was not possible. Instead, courses were offered in digital form. The sudden change posed enormous challenges to universities, students, and teachers. The aim of this study was to investigate the disadvantages as well as the advantages and opportunities of digital learning. Objective This study investigated the evaluation of an elective module by medical students and teachers in the traditional in-person and virtual teaching forms during the COVID-19 pandemic. Methods Using the elective module “Sports Medicine,” which includes both lectures and practical units, the opinions of the medical students about conventional teaching compared to digital instruction were evaluated. In the winter semester of 2019/2020, all classes were taught face-to-face but had to be switched to virtual teaching in the summer semester of 2020 on an ad hoc basis due to the pandemic. The students were asked to answer questions on general conditions, participant behavior, instructor evaluation, skill acquisition, topic selection, and overall evaluation after both forms of teaching. Likewise, the lecturers of both courses were queried in semiqualitative interviews about the same topics. Descriptive data analysis was performed to process the data. Results The students perceived digital teaching to be superior in most subareas compared to in-person teaching in terms of framework, instructor evaluation, skill acquisition, topic selection, and overall rating. Medical students seemed to feel better with digital teaching in most areas of evaluation. The lecturers found the new form of teaching rather unsettling and criticized the lack of verbal and especially nonverbal communication as well as the short preparation time for the new challenge. The instructors were uncomfortable with some aspects of the virtual teaching format. Conclusion In the wake of the COVID-19 pandemic, medical schools should rapidly digitize their teaching offerings and support faculty members in their computer-based competence with continuing education opportunities and time resources.